The Impact of Sleep Hygiene on Cognitive Functioning, Mental Health, and Physical Performance in Young Adults: A Narrative Review of the Literature - Romaniuk, Patryk; Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Journal of Education, Health and Sport, 2026)
Sleep hygiene encompasses behavioral and environmental practices that shape sleep quality and circadian stability. Among young adults, lifestyle demands, academic pressures, and widespread digital media use contribute to irregular sleep–wake schedules, shortened sleep duration, and increasing sleep disturbances. This narrative review synthesizes research from sleep medicine, psychology, and public health to examine how sleep hygiene relates to cognitive performance, psychological well-being, and physical functioning in young adults. Evidence indicates that inconsistent sleep timing, evening light exposure, and stimulating pre-sleep activities are linked to impaired attention, reduced learning efficiency, and poorer executive functioning. Poor sleep hygiene is also associated with heightened emotional reactivity, greater risk of anxiety and depressive symptoms, and impaired stress regulation. Physiological consequences include altered neuroendocrine rhythms, reduced recovery capacity, and declines in physical performance. Intervention studies show that adopting regular sleep schedules, minimizing nocturnal screen exposure, and optimizing sleep environments can improve sleep quality, daytime functioning, and mental health. Taken together, sleep hygiene emerges as a modifiable and cost-effective determinant of health in young adults. Integrating sleep-supportive behaviors into preventive medicine, education, and public health initiatives may help protect cognitive, emotional, and physical functioning during this critical developmental period.